Undeveloped till soils in scree areas are an overlooked important phosphorus source for waters in alpine catchments - Kaňa, Jiří; Kaštovská, Eva; Choma, Michal; Čapek, Petr; Tahovská, Karolina; Kopáček, Jiří (Scientific reports, 2023)
Scree deposits in alpine catchments contain undeveloped till soils that are "hidden" between and under stones. These scree areas have no vegetation except for sparse lichen patches on stone surfaces, but the soils exhibit biological activity and active cycling of nitrogen (N), phosphorus (P), and organic carbon (C). We compared the chemical and biochemical properties of till soils in the scree areas (scree soils) with developed soils in alpine meadows (meadow soils) of 14 catchments in the alpine zone of the Tatra Mountains. The data showed that scree soils served as an important source of mobile P forms for waters in high elevation catchments. We then conducted a detailed soil survey focused on four selected alpine catchments with scree cover proportions > 30%. This study confirmed that scree soils have significantly higher concentrations of mobile P forms compared to meadow soils, and a high specific microbial activity directed towards the extraction of P with rapid turnover in the microbial biomass. The combination of these properties and the amounts of scree soils in high-elevation areas highlight their importance in overall biogeochemical P cycling in alpine catchments, and the terrestrial P export to receiving waters.
Keywords: Carbon; biomasa; Bicycling; Biomass; fosfor; Soil; Phosphorus; uhlík; půda; cyklistika